1993
DOI: 10.1038/365179a0
|View full text |Cite|
|
Sign up to set email alerts
|

c-Jun is essential for normal mouse development and hepatogenesis

Abstract: The proto-oncogene c-jun is the cellular homologue of v-jun, the transforming oncogene of the avian sarcoma virus 17 (ref. 1). c-jun encodes one major component of the AP-1 transcription factor complex and is expressed in many organs during mouse development and in the adult. Because of its rapid induction in cells following growth stimulation and the presence of AP-1 binding sites in the promoter regions of many genes, the c-Jun protein is thought to have important functions in cell proliferation and differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
340
1
4

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(359 citation statements)
references
References 16 publications
12
340
1
4
Order By: Relevance
“…In addition, microinjection of antibodies against c-Jun was shown to inhibit progression of cells from G1 into S phase (Kovary and Bravo, 1991). Studies employing ®broblasts and/or hepatoblasts from c-jun knockout mice demonstrated that c-Jun de®ciency results in a severe proliferation defect, which cannot be compensated by addition of puri®ed mitogens (Eferl et al, 1999;Hilberg et al, 1993;Johnson et al, 1993). Thus, at least in cultured ®broblasts and hepatoblasts, c-Jun acts as a positive regulator of cell growth.…”
Section: C-jun and Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, microinjection of antibodies against c-Jun was shown to inhibit progression of cells from G1 into S phase (Kovary and Bravo, 1991). Studies employing ®broblasts and/or hepatoblasts from c-jun knockout mice demonstrated that c-Jun de®ciency results in a severe proliferation defect, which cannot be compensated by addition of puri®ed mitogens (Eferl et al, 1999;Hilberg et al, 1993;Johnson et al, 1993). Thus, at least in cultured ®broblasts and hepatoblasts, c-Jun acts as a positive regulator of cell growth.…”
Section: C-jun and Cell Proliferationmentioning
confidence: 99%
“…Mice (Behrens et al, 1999;Erfel et al, 1999;Hilberg et al, 1993;Johnson et al, 1993;Schreiber et al, 1999;Wisdom et al, 1999) c-JunAA Viable As above As above (Behrens et al, 1999) (Ganiatsas et al 1998;Nishina et al, 1996aNishina et al, ,b, 1998Nishina et al, , 1999Yang et al, 1997a) Cellular responses to c-Jun and JNK signaling S Leppa È and D Bohmann lacking the c-Jun phosphorylation sites Ser 63 and 73 show no defects in several forms of normal developmentally regulated apoptosis (Behrens et al, 1999). Even in the complete absence of c-Fos and c-Jun in double knockout mouse embryos, no defects in the normally occurring developmentally programmed cell death were recorded (Ro er-Tarlov et al, 1996).…”
Section: Jun As a Mediator Of Apoptosismentioning
confidence: 99%
“…The liver degeneration phenotype observed in FIP200 KO embryos is similar to the KO embryo phenotypes by deletion of several components in TNFα survival signaling pathways including Rel A, IKK-β, IKK-γ, GSK-3, MKK4, MKK7, or c-Jun, which are characterized by mid/late gestational lethality associated with increased apoptosis in liver [41][42][43][44][45][46][47]. Furthermore, FIP200 KO MEFs exhibit increased apoptosis upon TNFα treatment, which might be explained by the loss of FIP200 interaction with ASK1 and TRAF2, regulation of TRAF2-ASK1 interaction and ASK1 phosphorylation [12].…”
Section: The Role Of Fip200 In Embryonic Developmentmentioning
confidence: 73%
“…These include the binding motif for activator protein 1 (AP1) which has shown to be involved in cell proliferation, differentiation and tumourigenesis, 44 upstream regulatory factor 1 (USF1) which has defined roles in regulation of genes expressed in the liver 45 and spleen focus forming virus proviral integration oncogene 1 (SPI1) which plays a role in the development of myeloid and b-lymphoid cells which are important during an immune response. 46 The functional importance of these TFs in regulation of CP expression should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%